The Green Screen as the Sixth Biome - Braga, Catarina (Revista de Comunicação e Linguagens, 2024)
Post-post-nature is a term that I first introduced in the master’s thesis “Post Post-Nature — The Technological Mediation between Humans, Plants, and Plant Images” (2022) so as to characterise a new kind of nature: the digital nature of plant images.